Coping with the COVID-19 pandemic by Paralympic athletes preparing for elite sport events: A longitudinal study - Urbanski, P. K.; Rogoza, R.; Brewer, B.; Tasiemski, T. (Scandinavian Journal of Medicine & Science in Sports, 2023)
Introduction This study investigates the impact of the COVID-19 pandemic on mental health, coping styles and their relationship, and training opportunities in elite athletes with disabilities (AwD) preparing for national and international sport events during a ten-month observation period.